Proceedings of the Genetic and Evolutionary Computation Conference 2019
DOI: 10.1145/3321707.3321841
|View full text |Cite
|
Sign up to set email alerts
|

Gin

Abstract: Genetic improvement (GI) is a young ield of research on the cusp of transforming software development. GI uses search to improve existing software. Researchers have already shown that GI can improve human-written code, ranging from program repair to optimising run-time, from reducing energy-consumption to the transplantation of new functionality. Much remains to be done. The cost of re-implementing GI to investigate new approaches is hindering progress. Therefore, we present Gin, an extensible and modiiable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…There are many profiling tools available for Java. Gin versions up to v2.0 (White, 2017;Brownlee et al, 2019) made use of the HPROF tool (Oracle Systems, 2020) included with JDK versions up to 8. Watkinson and Brownlee (2023) summarised the desirable qualitative properties of several current profiling tools with a view to upgrading Gin for newer versions of Java.…”
Section: Profiler Integration With Ginmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many profiling tools available for Java. Gin versions up to v2.0 (White, 2017;Brownlee et al, 2019) made use of the HPROF tool (Oracle Systems, 2020) included with JDK versions up to 8. Watkinson and Brownlee (2023) summarised the desirable qualitative properties of several current profiling tools with a view to upgrading Gin for newer versions of Java.…”
Section: Profiler Integration With Ginmentioning
confidence: 99%
“…Instead, profiling appears to be often done by the respective team on an ad-hoc basis and with a variety of tools due to the targeted applications and objectives. For example, Haraldsson et al (2017) (White, 2017;Brownlee et al, 2019), which forms the focus of the present study, was developed with the aim to facilitate GI research. Gin is opensource, meaning researchers can build upon the existing code, and as far as possible makes use of multiple existing tools such as EvoSuite (Fraser and Arcuri, 2011) for automated test creation.…”
Section: Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…We used the genetic improvement toolbox Gin v2.0 [6] in our experiments. Gin fulfills all our requirements: it is open-source, targets Java programs, uses runtime improvement as fitness by default, and its second release provides integration with EvoSuite [11].…”
Section: Dataset and Toolsmentioning
confidence: 99%
“…Unlike in the automated program repair field, there is no standard benchmark for runtime improvement using GI. We also require the programs to be relatively small, so we could run thousands of experiments in reasonable time and avoid the, often very costly, profiling stage of the GI process [6], targeting the whole software instead. With those restrictions in mind, we chose to use the set of 9 sort algorithms and the triangle example provided with the first release of Gin [23] in our study, for which improvements have previously been found using GI [9].…”
Section: Dataset and Toolsmentioning
confidence: 99%